Manajemen Kelembagaan dan Akademik Lembaga Pendidikan Maarif Nahdlatul Ulama Kota Samarinda Kalimantan Timur - AR, Abdurrahman (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
TheEducational Management and Academic Of Ma’arif Nahdlatul Ulama in Samarinda, East Kalimantan, is to coming up a moeslem organization in the educational prospective and progressive mutual organization and education to come up image of Nahdlatul Ulama as the biggest moeslem organization in Indonesia.The objective of this research was to identificate the Educational management and Academic quality and to doctrine the religious values to the basic Ma’arif Nahdlatul UlamaInstitute in Samarinda, East Kalimantan. This research also designed to get the object datas from the three Islamic Elementry schools which organized by Ma’arif Nahdlatul Ulama Samarinda through many kind ways they are; (1) Interviews Elementry head masters and their commitees, (2) pictures, (3) school’s data or documents.The purpose of data collection wants to understand the Moslem Elementry School of Ma’arif Nahdlatul Ulama conditions in the some areas in Samarinda in order to know what are the weakness and lack of Ma’arif NU. The result of dataanalysis indicated three of Moslem Elementry School Ma’arif NU thoselocated in Samarinda city, they are MI 01 in Palaran, MI.02 Sindang Sari, MI 03 Jln. Rukun Samarinda Seberang, they still run in slowly.The researcher’s summary in this research those, from three of Madrasah Ibtidaiyyah of Educational Institute Ma’arif NU still need high supports from everyone, from moeslem who love education progressive now and the future.